2010
DOI: 10.1099/vir.0.020990-0
|View full text |Cite
|
Sign up to set email alerts
|

Bovine viral diarrhea virus non-structural protein 5A interacts with NIK- and IKKβ-binding protein

Abstract: Bovine viral diarrhea virus (BVDV) is a positive-sense, single-stranded RNA virus that causes an economically important livestock disease worldwide. Previous studies have suggested that nonstructural protein 5A (NS5A) from hepatitis C virus (HCV) and BVDV plays a similar role during virus infection. Extensive reports are available on HCV NS5A and its interactions with the host cellular proteins; however, the role of NS5A during BVDV infection remains largely unclear. To identify the cellular proteins that inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 44 publications
3
35
0
1
Order By: Relevance
“…For HCV, the NS5A-TRAF2 protein complex has been shown to inhibit TNF-induced NF-B activation, thereby increasing cellular resistance to apoptotic stimuli (68), perhaps modulating host responses to pathogens, persistence of viral infection, and disease severity (69). An inhibitory effect by NS5A-protein complexes on TNF-induced NF-B activation has also been reported for BVDV, albeit mediated through NS5A-binding interactions with different host immunomodulatory proteins (70).…”
Section: Discussionmentioning
confidence: 95%
“…For HCV, the NS5A-TRAF2 protein complex has been shown to inhibit TNF-induced NF-B activation, thereby increasing cellular resistance to apoptotic stimuli (68), perhaps modulating host responses to pathogens, persistence of viral infection, and disease severity (69). An inhibitory effect by NS5A-protein complexes on TNF-induced NF-B activation has also been reported for BVDV, albeit mediated through NS5A-binding interactions with different host immunomodulatory proteins (70).…”
Section: Discussionmentioning
confidence: 95%
“…This interaction was suggested to play a role in the replication of BVDV (Johnson et al 2001). In addition, Y2H screening identified bovine NIK-and IKK -binding protein (NIBP), which is involved in protein trafficking and nuclear factor kappa B (NF-κB) signalling in cells (Zahoor et al 2010). The interaction of NS5A with NIBP was confirmed both in vitro and in vivo.…”
Section: Virus-host Interacting Partnersmentioning
confidence: 93%
“…The same study also showed that inhibition of endogenous NIBP by RNAi enhanced virus replication, indicating the importance of NIBP in BVDV pathogenesis. This is the first reported interaction between NIBP and a viral protein, suggesting a novel mechanism whereby viruses may subvert host-cell machinery for mediating trafficking and NF-κB signaling (Zahoor et al 2010). Efficient generation of NS2-3 cleavage product NS3 is required for the cytopathogenicity of the pestiviruses.…”
Section: Virus-host Interacting Partnersmentioning
confidence: 99%
“…Myc-tagged NS4B gene was subcloned into the pCAGGS mammalian expression plasmid, named pCAG-NS4B, between XhoI and BglII sites. The plasmids pME-NS3 and pCAG-NS5A were described previously Zahoor et al, 2010). The NS4A gene sequence derived from Nose strain was generated using primers with NdeI and PstI sites at the 5´ and 3´ ends, respectively, and cloned into the plasmid pME18S-myc, named pME-NS4A.…”
Section: Plasmid Constructionmentioning
confidence: 99%